Social Welfare of People with Disabilities in Palembang City - Nurrahma, Justin; Giyarsih, M.Si., Sri Rum; Mulyani, Raden Rara Wiwik Puji (Universitas Lambung Mangkurat, 2024)
Social welfare is a condition that must be realized for the entire society. Therefore, every country must specifically fulfill the needs of its societal sectors according to the conditions and challenges they face. Social welfare also need to ralized for groups of people with special limitations, both physical and mental, commonly known as people with disabilities. In Indonesia, the understanding and provision of opportunities for the welfare of people with disabilities are not fullfill yet, the existence of individuals with disabilities is overlooked often, but there are groups of disabilities who have been able to achieve social welfare. This research aims to understand the conditions of disability welfare in Palembang and the efforts they make to achieve it. This study utilizes a descriptive qualitative method, with primary data gathered through interviews using purposive sampling techniques and secondary data obtained from document studies technic. The results show that disabilities who have successfully attained social welfare in Palembang are those with physical and sensory impairments, as they mental and brain function still work normally. They are able to access education, training, socialize with the general community, and work according to their type of disability, with efforts originating from themselves, their families, and social assistance. The most important aspect in realizing social welfare is the motivation and spirit from within the individuals and their families who have disabilities.